Evidence of social and environmental vulnerability in Sepetiba Bay: an analysis of risk situations - doi:10.5020/18061230.2009.p209 - Aldo Pacheco Ferreira (Universidade de Fortaleza, 2012)
Objective: To identify, among the population of Sepetiba Bay, risk situations of environmental vulnerability. Methods: Data collection was performed through a self-administered questionnaire with open and closed questions in a determined population of 895 subjects, between 2007 and 2009. The techniques used consisted of semi-structured interviews, structured questionnaires and participant observation (triangulation of methods). After the validation of the instrument by stages (face validity, content validity and construct validity),the main risks reported by the subjects were determined. Results: A total of 675 environmental risk situations was detected, especially the contamination of the water, soil and air; the waste; the impact on flora and social demands. It was observed that the same risk may simultaneously affect more than one location, emphasizing that one same problem was mentioned in more than one location of the bay. Conclusions: The results support the hypothesis guiding the research that the environment is part of the culture of a particular community or group as a process of interaction between cultural and natural environment.